PENGARUH PENGETAHUAN PERPAJAKAN, SELF-EFFICACY, DAN PERTIMBANGAN PASAR KERJA TERHADAP MINAT MEMILIH KARIER KONSULTAN PAJAK - Muhamad Ansorudin; Vivi Iswanti Nursyirwan (Publika Citra Media, 2026)
This study aims to analyze the influence of tax knowledge, self-efficacy, and job market considerations on the interest in choosing a tax consultant career among students at Pamulang University, South Tangerang. The research sample consisted of 199 7th and 8th semester Accounting students majoring in taxation, determined using the Krejcie-Morgan Table at a 10% error rate. Primary data were obtained through a questionnaire that had been tested for validity and reliability, using a direct survey method. Data analysis used classical assumption tests, simple and multiple linear regressions, and hypothesis testing with SPSS version 25. The results showed that tax knowledge and job market considerations had a significant effect on interest in choosing a tax consultant career, while self-efficacy had no effect. Simultaneously, tax knowledge and job market considerations were proven to influence this interest.